1995
DOI: 10.4037/ajcc1995.4.2.143
|View full text |Cite
|
Sign up to set email alerts
|

Effects of three methods of femoral site immobilization on bleeding and comfort after coronary angiogram

Abstract: BACKGROUND: Postangiogram femoral site care varies by institution and practitioner. The literature is unclear about which intervention provides the best hemostasis and patient comfort. OBJECTIVE: To investigate which method of femoral site immobilization results in less bleeding and more comfort after coronary angiography. METHODS: Three hundred inpatients and outpatients undergoing coronary angiography in a large, metropolitan, tertiary care facility were assigned randomly to three types of femoral site immob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…The values of Cronbach's alpha (α) ranged from 0.74 -0.82. The structural validity of the questionnaire, which was tested with exploratory factor analysis, confirmed the single factor structure of the questionnaire [9,10].…”
Section: Study Instrumentsmentioning
confidence: 74%
See 1 more Smart Citation
“…The values of Cronbach's alpha (α) ranged from 0.74 -0.82. The structural validity of the questionnaire, which was tested with exploratory factor analysis, confirmed the single factor structure of the questionnaire [9,10].…”
Section: Study Instrumentsmentioning
confidence: 74%
“…However, in the available literature there are not many studies which have examined the level of comfort related to the immobilization used. Most of the studies evaluated the level of pain in the postoperative recovery using visual analogue (VAS) and verbal rating scale (VRS) or by assessing comfort theory and validity [9,10,12]. Thus, Howlin et al [12] assessed the level of comfort of head restraints and thermoplastic masks during radiotherapy only by VAS scale.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no standardized tool for assessing the degree of discomfort they feel during hospitalization. This methodological study was designed to apply the ICQ, which has been found to be valid and reliable for assessing patients undergoing coronary angiography [37], to the orthopedics and traumatology clinics and test its validity and reliability with a new population. Given that ICQ is not a commonly used tool, the literature review did not reveal any studies with which to cross-check our study results.…”
Section: Discussionmentioning
confidence: 99%
“…The validity and reliability study of the ICQ was conducted by Hogan-Miller, Rustad, Sendelbach, and Goldenberg [37], with contribution from Kolcaba, and included patients undergoing coronary angiography who were immobilized. Cronbach a was .74 for the first assessment and .67 for the second assessment [37]. No other studies using the ICQ were found during the literature search.…”
Section: Icqmentioning
confidence: 99%
See 1 more Smart Citation